Optimization of ethyl ester production from olive and palm oils using mixtures of immobilized lipases - Poppe, Jakeline K.; Matte, Carla R.; Ruaro Peralba, Maria do Carmo; Fernández-Lafuente, Roberto; Rodrigues, Rafael C.; Záchia Ayub, Marco A. (Applied Catalysis A: General, 2015)
Although reactions of transesterification are generally catalyzed by one specific lipase preparation, the concept of “combi-lipase” could be better explored for the production of biodiesel, since oils are heterogeneous substrates. In this research, we tested this concept by evaluating the enzymatic transesterification of olive and palm oils, two diverse fatty acid compositions, using standalone or mixtures of three immobilized lipases as biocatalysts: Novozym 435 (CALB), Lipozyme TL-IM (TLL), and Lipozyme RM-IM (RML). For olive oil, the combination of 29.0% of TLL, 12.5% of RML, and 58.5% of CALB was the best, allowing for 95% conversion efficiency in 18 h of reaction, up from 50% for the best individual lipase (CALB). For palm oil, the best enzyme combination was 52.5% of TLL and 47.5% of RML, resulting in 80% of conversion of ethyl esters in 18 h, compared to only 44% when standalone TLL was used. Repeated batches of reaction were carried out in order to test the operational stability of the combi-lipase systems, with results showing that they could be used for at least seven cycles keeping higher than 80% of their initial activities. This work was supported by grants from Brazilian Coordenação de Aperfoiçoamento de Pessoal de Nível Superior (CAPES) and CTQ2013-41507-R from Spanish MINECO. Peer Reviewed